The language image of the word "tree" in Vasyl Holoborodko’s poetry - Shleneva, M. G. (Society for Cultural and Scientific Progress in Central and Eastern Europe, 2016)
The article is devoted to the language image of the word "tree" in poetic texts of Vasyl Holoborodko. The image of the word "tree" is analyzed as an element of the poet’s language picture of the world. The interpretation of the language image of the word "tree" is considered in various forms: as element of the nature, as the personified image, as mythological figure, etc. The conclusion is drawn about the role of the language image of the word "tree" in the author’s language picture of the world.

Статья посвящена образу дерева в поэтических текстах Василя Голобородька. Образ дерева анализируется как элемент языковой картины мира поэта. Рассматривается интерпретация образа дерева в различных ипостасях: как природного элемента, как персонифицированного образа, как мифологической фигуры и т.д. Делается вывод о роли образа дерева в поэзии автора.
Языковой образ дерева в поэзии Василя Голобородько
Keywords: language image of the word "tree"; poetry; language picture of the world; образ дерева; поэзия; языковая картина мира